The Effectiveness of Thematic Learning through the Cooperative Learning Approach of Team Accelerated Instruction (TAI) in Grade IV of SDN Cengkareng Barat 11 - Fadli, Muhammad Rijal; Fatonah, Khusnul; Afwan, Bahtiar; Qurrotu’ain, Rofifah (Universitas Pattimura, 2025)
This study aimed to improve motivation and academic achievement of fourth-grade students at SDN Cengkareng Barat 11 Jakarta by applying the Cooperative Learning model, Team Accelerated Instruction (TAI), in thematic learning on Theme 8: